Pemanfaatan Sistem Informasi Digital Menggunakan Kerangka Kerja People Process Technology - Wulansari, Eka; Takwim, Ahsani (JESII: Journal of Elektronik Sistem InformasI, 2025)
This study examines the utilization of digital information systems in Indonesia from a national perspective using a descriptive quantitative approach and national digital indicators interpreted through the People–Process–Technology framework. The findings indicate that digital information systems in Indonesia demonstrate strong utilization in terms of user participation and technology adoption, particularly through mobile-based access. These results confirm that digital technologies have become an essential part of daily activities and function as mainstream infrastructures at the national level. However, the analysis also reveals that infrastructure readiness and supporting processes have developed at a slower pace compared to user adoption and technological access. This imbalance may limit the effectiveness and consistency of digital information system utilization, despite high levels of access. From a People–Process–Technology perspective, the people and technology dimensions appear relatively strong, while the process dimension represents the primary constraint. Overall, the study concludes that effective utilization of digital information systems requires balanced development across people, process, and technology dimensions to fully maximize the benefits of widespread digital adoption in Indonesia.